2022
DOI: 10.21474/ijar01/15711
|View full text |Cite
|
Sign up to set email alerts
|

Ways to Learning Science Are Undergoing Mutation: Would the Culturo-Techno-Contextual Approach Be an Effective Variant for Learning Chemistry?

Abstract: As the quest for better ways to present science to the new generation of students continues to occupy the thoughts of science educators across the globe, so will new approaches such as the Culturo-Techno-Contextual Approach (CTCA) continue to emerge in response to thisquest. This study explores the potency of CTCA in breaking the barriers to meaningful learning of electrochemistry. The explanatory sequential design was employed. A total of 141 secondary school (II) students from two purposively selected school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…While there could be other factors responsible for the observed difference, the teaching strategy employed in the experimental groups appeared first on the list of suspects. This result shares semblance with the findings of [2,75]. Both studies found CTCA as an active agent that promotes students' interest in science learning.…”
Section: Effects Of Ctca On Students' Anxiety Level In Learning Chemi...supporting
confidence: 84%
“…While there could be other factors responsible for the observed difference, the teaching strategy employed in the experimental groups appeared first on the list of suspects. This result shares semblance with the findings of [2,75]. Both studies found CTCA as an active agent that promotes students' interest in science learning.…”
Section: Effects Of Ctca On Students' Anxiety Level In Learning Chemi...supporting
confidence: 84%
“…Since 2015 when CTCA was officially launched, it has received growing attention in science education in Nigeria and is currently gaining recognition in international research communities through conference presentations and journal publications (Ademola et al, 2023; Onowugbeda et al, 2022). CTCA is considered an egalitarian approach (Oladejo et al, 2022b), coming in at a time when the global call for inclusion, diversity and equity in STEM education is a major focus. The extent to which equity, inclusion and diversity are achieved is a function of how well the marginalized or least‐served population is better served in terms of skill and knowledge dispensary.…”
Section: The Culturo‐techno‐contextual Approachmentioning
confidence: 99%
“…Since 2015 when CTCA was officially launched, it has received growing attention in science education in Nigeria and is currently gaining recognition in international research communities through conference presentations and journal publications (Ademola et al, 2023;Onowugbeda et al, 2022). CTCA is considered an egalitarian approach (Oladejo et al, 2022b), coming in at a time when the global call for inclusion, diversity and…”
Section: The Culturo-techno-contextual Approachmentioning
confidence: 99%